PENGARUH SUPLEMENTASI Chlorella vulgaris PADA PAKAN UNTUK MENINGKATKAN ALBUMIN DALAM SERUM IKAN NILEM (Osteochilus vittatus) - Zakiah, Kiki Siti; Simanjuntak, Sorta Basar Ida; Wibowo, Eko Setio (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2020)
Nilem fish belongs to freshwater fish commodity that has been widely cultivation. Some factors influencing fish cultivation are good quality of feed, quantity, size, and shape. Quality feed works as a primary energy source as well as improves the digestive system of fish, with the expectation that the fish growth and health are optimal. Information concerning health status in cultivation Nilem has been used as a reference for improving cultivation methods and controlling disease attacks. The population and production of fish cultivation is experiencing serious problems due to infection from various types of pathogens. Therefore, a viable alternative is needed to prevent and overcome diseases by utilizing immunostimulant substances derived from synthetic substances that can increase the activity of non-specific immune defenses and stimulate antibiotic-forming organs in fish body. Immunostimulant is a substance that is capable of increasing the mechanism of non-specific immune response of fish one of them is by adding Chlorella vulgaris extract to the feed. This research objective is to determine the influence of Chlorella vulgaris supplementation on total blood albumin in nilem fish. This research was conducted by sampling method consisting of 5 treatments with further 4 replications. The treatments were feed supplementation of 0 g.kg-1, 2 g.kg-1, 3 g.kg-1, 4 g.kg-1, and 6 g.kg-1. Independent and dependent variables were used in this research; the independent variable was the dose of Chlorella vulgaris in the feed and the dependent variable was blood albumin concentration. The measuring of plasma albumin concentration was done using the Dyasis kit method with a spectrophotometer. The obtained data were then analyzed by ANOVA, followed by the Least Significant Difference (LSD) at the 95% confidence level if there is a real difference then followed by Tukey's test at the same confidence level. The results showed that the average value of serum albumin concentration of nilem fish from all treatments was between 4.2761 – 7.1826 g/dL. The normal albumin concentration was found in the treatment 4 g.kg-1 Chlorella vulgaris supplementation which was 4.77 g/dL. Meanwhile, the highest concentration was found from the supplementation of Chlorella vulgaris at 3 g.kg-1 feed which was 6.677 g/dL.